The genus Zhengitettix Liang, 1994 (Orthoptera: Tetrigidae: Scelimeninae) from Thailand, with description of a new species - Dawwrueng, Pattarawich; Vitheepradit, Akekawat (Zootaxa, 2024)
Four species of the genus Zhengitettix Liang, 1994 from Thailand are listed. A new distribution of Z. albitarsus Storozhenko, 2013 is reported from Ratchaburi Province in the Tenasserim Range with a coloration description of live specimens. Z. binduseni sp. nov. is described from Ratchaburi Province, Thailand. This new species is easily distinguished from other member in this genus by the larger body size, the fastigium of vertex between eyes distinctly narrower toward end, the slender and long spines of lower part of lateral lobe of pronotum which slightly upward in male, and almost straight in female, and the shaped of female subgenital plate with shallow transversal creases. The updated key to all species occurring in Thailand is provided here.